Convective Heat Exchange General Concepts - Siddikov Rasuljon Uktamovich; Bakhriddinova Dilnora Sharifjon kizi; Mirzayev Islambek Umarali ugli; Abdusattorov Axadjon (Scientific Trends, 2023)
Convective heat exchange is the transfer of heat through the movement of fluids or gases. This process is very important in many fields such as engineering, physics, geophysics, meteorology, and more. Convective heat transfer occurs by forced convection, where fluids or gases are forced to move by external means such as fans or pumps, and by natural convection, where the motion of fluids or gases arises solely from density differences caused by temperature gradients. This article aims to provide a comprehensive overview of convective heat exchange by discussing the basic principles, the different types of convective heat transfer, the relevant mathematical formulas, and several real-world applications.